Prenatal diagnosis of dicentric chromosome X mosaicism: a case report and review - Wang, Rong Hua; Wu, Ke; Hu, Xiao Ling (Frontiers in Genetics, 2024)
A dicentric chromosome is an abnormal chromosome with two centromeres on the same chromosome. It have been reported that dicentric chromosomes are specific biomarker of radiation exposure, but dicentric chromosomes are rarely identified in newborn with multiple congenital anomalies. At 16 weeks of gestation, a 39-year-old pregnant woman (gravida 2, para 1) was referred to the prenatal diagnosis center for genetic counselling. The fetal ultrasonography indicated multiple anomalies.Subsequently, amniocentesis was performed, the G-banding karyotype analysis showed a rare type of mosaicism. The C-banding karyotype analysis indicated a pseudo dicentric chromosome X [psu dic(X;18)(p11.2;p11.2)]. Single nucleotide polymorphism array (SNP array) revealed three pathogenic copy number variations (CNVs). After genetic counselling, the parent chose to terminate this pregnancy. This study provides new evidence for a better understanding of the diagnosis of dicentric chromosomes and emphasizes the importance of genetic counseling.